MODELING OF THE PROCESS OF BIOLOGICAL WASTEWATER TREATMENT BASED ON CHAMBER MODELS - Lemesh, M. V.; Biliaiev, M. M.; Tatarko, L. H.; Yakubovska, Z. M. (Science and Transport Progress, 2020)
Purpose. The aim of the work is to develop multifactor chamber models for rapid evaluation of the efficiency of reactors for biological wastewater treatment. Methodology. Two numerical chamber models have been developed for computer simulation of the biological wastewater treatment process. The models are based on the law of mass conservation for substrate and activated sludge. The models are zero-dimensional. In the first chamber model, the pollutant oxidation process is calculated based on a first-order reaction. The second chamber model uses the Monod model to calculate pollutant oxidation. Euler’s method is used for numerical integration of modeling equations. The models allow, when calculating the bioreactor, to take into account the change over time in the concentration of activated sludge, the substrate entering the reactor for biological wastewater treatment. Findings. The software implementation of the developed numerical models is carried out. The results of computer experiments to study the efficiency of wastewater treatment in reactors for biological wastewater treatment for different operating conditions are presented. Originality. Two computer chamber models have been developed to quickly evaluate the efficiency of a bioreactor for wastewater treatment under different operating conditions. Practical value. The developed computer models can be used to determine the efficiency of biological wastewater treatment in reactors under different operating conditions.